Can forward interest rates predict future spot rates in South Africa? A test of the pure expectations hypothesis and market efficiency in the South African government bond market - Loukakis, Andrea (My University, 2012)
The pure expectations hypothesis says that forward rates, implied off a yield curve, are unbiased predictors of future spot rates. Which implies forward rates, according to the pure expectations hypothesis, should provide reliable forecasts of future spot rates. This study set out to see if the theory behind the pure expectations hypothesis holds in a South African context. If it does hold, it can have an impact on real world applications such as bond trading strategies and the setting of monetary policy. To test the theory behind the pure expectations hypothesis, South African government bond data for the short end of the yield curve was used. Various regression tests were run. These regressions tested mainly for forward rate forecast accuracy, the relationship between forecast errors and changes in the spot rate, for the presence of liquidity premiums and to test for market efficiency. The results indicated that forecast accuracy and the relationship between forecast errors and changes in the spot rate were contrary to the theory behind the pure expectations hypothesis. A liquidity premium was found to exist and there appeared to be weak form market efficiency. These results led to a conclusion that there is very little evidence to support the theory behind the pure expectations hypothesis. This was mainly due to the presence of a liquidity premium. The pure expectations hypothesis does not seem to be of any significant use within real world applications.
Keywords: Interest rates; Forecasting